A dermoscopic study of nail involvement in chronic plaque psoriasis at a tertiary care center - Kesiezie, Neikhrietsonuo; Zacharia, Meriya; R, Aswini (Asian Journal of Medical Sciences, 2022)
Background: Psoriasis is a chronic inflammatory disease that affects millions of people throughout the world. Nail involvement is a common feature in psoriasis which is often overlooked despite causing significant functional impairment, disfigurement, and psychological stress to the patient. Dermoscopy is a non-invasive novel tool that enables a rapid and magnified visualization of the nail changes which are often imperceptible to the unaided eye. Aims and Objectives: To study the dermoscopic profile of nail changes in patients with chronic plaque psoriasis. Materials and Methods: The study was conducted from December 2018 to May 2020, in the Department of Dermatology of a tertiary care center in Kerala, including 155 patients of clinically diagnosed chronic plaque psoriasis who had nail involvement. A detailed history was noted along with a clinical and dermoscopic examination of all 20 nails of each patient. Results: The most common finding on dermoscopic examination of the nails was onycholysis seen in 91%, followed by pitting (78.8%) and subungual hyperkeratosis (78.1%). Other findings noted in our study which are not commonly described are wavy lamellar microsplitting (41.9%), cuticular hypertrophy (18.1%), pseudofiber sign (16.1%), dilated nailfold capillaries (12.3%), capillary prominence at onychodermal band (7.7%), dilated hyponychial capillaries (7.7%), and fuzzy lunula (7.1%). Conclusion: Nails are frequently involved in psoriasis but often overlooked. Dermoscope is an effective tool that facilitates the assessment of nail changes in psoriasis.